"He got a glimpse of the joys of understanding" – The role of epistemic empathy in teacher learning. Issue 3 (27th May 2021) - Jaber, Lama Z.
ABSTRACT: Background: Efforts to promote reform-based instruction have overlooked the import of affect in teacher learning. Drawing on prior work, I argue that teachers' affective experiences in the discipline are integral to their learning how to teach the discipline. Moreover, I suggest that both affective and epistemological aspects of teachers' experiences can serve to cultivate their epistemic empathy —the capacity for tuning into and valuing someone's intellectual and emotional experience within an epistemic activity—in ways that support student-centered instruction. Methods: Using a case study approach, I examine the learning journey of one preservice teacher, Keith, who after having expressed strong skepticism about responsive teaching, came to value and take up responsive teaching in his instruction. Findings: The analysis identifies epistemological and affective dynamics in Keith's interactions with students and in his relationship with science that fostered his epistemic empathy. By easing his worries about arriving at correct answers, Keith's epistemic empathy shifted his attention toward supporting students' sensemaking and nurturing their relationships with the discipline. Contributions: These findings highlights teachers' affective experiences in the discipline as integral to their learning how to teach; they also call attention to epistemic empathy as an important aspect of and target for teacher learning.